LEGAL REVIEW OF THE DIVISION OF JOINT PROPERTY IN MARRIAGE BASED ON THE PERSPECTIVE OF CIVIL LAW - Novi Juli Rosani Zulkarnain (Bajang Institute, 2026)
This study examines the legal review of the division of marital property from a civil law perspective. The main focus of this study is to analyze how the concept of marital property is understood and applied in legal practice in Indonesia, and how the balance between legal certainty and substantive justice is realized in the resolution of marital property disputes. The method used in this study is normative juridical with a statutory, conceptual, and case study approach to court decisions related to joint property. The results of the study indicate that the regulation of joint property in marriage cannot be separated from the construction of marriage law, which places husband and wife in equal positions as legal subjects. The concept of joint property in the Indonesian legal system is also pluralistic due to the influence of customary law, Islamic law, and Western civil law, but there is a common ground in the recognition of joint contributions in the formation of assets during marriage. Furthermore, it was found that the division of joint property in judicial practice is not always carried out equally, but rather takes into account the actual contributions of each party, both economic and non-economic. This study also found inconsistencies in decisions in joint property cases due to the lack of standard provisions that regulate in detail the proportion of distribution based on the parties' contributions. This situation creates potential legal uncertainty, while also providing judges with discretion to apply substantive justice based on the facts of the trial. Therefore, harmonization and more operational guidelines are needed for the division of joint assets to ensure consistent court decisions. The conclusion of this study is that the division of joint assets, from a civil law perspective, is the result of the interaction between legal norms, judicial practices, and social dynamics. Therefore, a balance between legal certainty and substantive justice is necessary so that the family law system in Indonesia can provide fair, consistent, and responsive protection to societal developments.